Unmanned Aerial Vehicles Base Station Performance Analysis In Wireless Communications (Journal of Technology Research, 2025)
Unmanned aerial vehicles (UAVs) are becoming increasingly popular for a variety of applications, including wireless communication. manoeuvrability, low cost, and Line of sight (LOS) communication make UAVs a promising candidate for future wireless communication networks. This paper reviews the classification of UAVs, and their use cases in wireless communication, and UAV channel modeling. Begins by exploring the primary types of UAV channel fading: large-scale fading and small-scale fading, then reviews the UAV channel characteristics and categories . Finally, this paper discusses the performance evaluation of UAV base stations regarding UAV coverage probability, optimal altitude, ideal elevation angle, and minimum transmission power. Our findings demonstrate that several factors, including the height and density of buildings, coverage radius, UAV altitude, and necessary network throughput, impact the optimal altitude, elevation angle, and minimum transmission power.
Keywords: unmanned aerial vehicles; path loss; channel modeling; UAV base station